Assessing phenological growth stages of barberry tree growth and the effect of climate change on its water requirement in Iran - Hasan Rezaei; Mohamad Motamedi Rad (مدل‌سازی و مدیریت آب و خاک, 2023)
Introduction Increasing the efficiency of water consumption and water management is necessary to meet the water needs of agricultural plants which need to consider the variables affecting water consumption, including water needs and the amount of evaporation and transpiration. In this regard, evaporation and transpiration are important indicators in the process of plant growth and their amount is considered equal to the water requirement of the plant. On the other hand, climate change can affect water demand by changing the expected patterns for the average weather condition in a long term in a specific region or for the entire global climate. In the present study, the phenological stages of seedless barberry tree were determined based on field observations at Ghaen synoptic meteorological station. The seedless barberry tree is one of the commercial cultivars in Iran. In this research, the effect of climate change on the water requirement of barberry cultivation has been evaluated based on RCP scenarios in the near and far future. Materials and Methods In the field part, in order to identify the occurrence time of the phenology stages and temperature thresholds, a series of visits and daily and weekly notes were made in the field in the growing season of the barberry tree. For this purpose, a private and fertile commercial orchard with suitable cultivated area of ​​seedless barberry trees was selected. The studied garden group with three hectares of cultivated area in Qain city was identified as one of the most fertile gardens in the region. This private garden is located in Qain city, at the position of 33 degrees and 43 minutes of north latitude and 59 degrees and 10 minutes of east longitude and a height of 1432 meters above sea level. In this study, the phenology stages of seedless barberry tree as one of the commercial cultivars of Iran were determined. The BBCH coding system was used to record the phenology stages (Enriquez‐Hidalgo et al., 2020). This scale has a 100-part table with codes from 0 to 99 and is designed for different phases (Feldmann and Rutikanga, 2021). It was used in the synoptic meteorological station of Qain city during one year from the beginning of germination to the end of the dormant period. In fact, the codes of the phenology stages were observed and recorded in the field.After determining the phenological stages of barren barberry trees, the water requirement of the selected tree species has been calculated. In the next step, to determine the water requirement, the reference evaporation and transpiration rate must be multiplied by the plant coefficient. For this purpose, the available data including hours of sunshine, average temperature during the growing season, average rainfall, minimum temperature, maximum temperature, evaporation, and transpiration obtained from the National Meteorological Organization for 18 valid meteorological stations from 1987 to 2017 on hourly and daily time scales were used to predict the climatic condition. Toward this, the climatic condition of the near future (2059-2030) and the far future (2089-2060) has been predicted considering pessimistic (RCP8.5), and optimistic (RCP4.5) scenarios. Results and Discussion The results showed that barberry needs six phenological stages to complete the growth period from early April to late November. Also, the amount of water requirement for barberry treesin the base period (1987-2017) on a daily basis in the eastern region under study is more than in the west and northwest of the region. The water requirement in the northwest and west parts is more than in the east of the region under study, which is the reason for the increase in the length of the barberry phenology stage in the region has been mentioned. The results of climate change analysis showed that the daily water requirement of barberry (2030-2059) based on the RCP8.5 model during the growing season varies between 4.5-5.8 mm per day and the total water requirement is 990-1260 mm. According to the RCP4.5 model, the daily water requirement of barberry varies between 5.6-5.8 mm per day and the total water requirement is 1290-990 mm. The daily water requirement of barberry according to the RCP4.5 model (2060-2089) varies between 4-5 mm per day and the total water requirement is 960-1150 mm. Also, the daily water requirement of barberry according to the RCP8.5 model varied between 4.5-8.2 mm per day. The total water requirement of the barberry tree is 950-1300 mm. ConclusionThe present study was conducted with the aim of measuring the phenology stages of the seedless barberry tree and the water requirement of the barberry tree according to the conditions of climate change in the areas prone to its cultivation in Iran. The results showed that the barberry tree needs six phenology stages to complete its growth cycle. The growth period according to climatic conditions and topography lasts from early April to late November. The results of estimating the water requirement in the base period showed that the cities of Kerman, Yazd, Qain, Birjand, Zahedan and Torbat Heydarieh need the most water during the growth stage (1330-1240 mm per day) and the lowest water requirement of the barberry tree in the north It is in the west and west of the country, but in the future, the amount of water needed by the barberry tree in the northwest and west is more than the center and east of the study area, which is the reason for the earlier completion of the phenology stages in the center and east of the country, for this reason, these areas are among the unsuitable areas. It is considered cultivation. Since the annual rainfall changes from year to year; Therefore, the irrigation project cannot be planned only based on one year's information, so long-term records are needed to calculate the effective rainfall based on the probability of occurrence. Cultivation of barberry is very desirable in terms of irrigation for dry and semi-arid areas where farmers are facing water shortage. Considering that water is the main and essential requirement of any product; Therefore, it is essential to estimate the water requirement of each plant.